Skin Beauty as Erotic Capital and Production of “Luckiness”: A Look at Menopausal Women Using Hormone Therapy Replacement for Skin Treatment in Ho Chi Minh City, Vietnam - Tam, Huynh Thi Xuan (Animo Repository, 2017)
According to social and cultural constructs of aging and femininity, menopausal women‘s bodily transitions cause them to initiate hormone therapy replacement (HRT) to restore their youth and beauty. For example, they might take HRT to improve their wrinkled and sagging skin. A problem emerges, however, because there is little systematic research that explains the specific factors that motivate women to take HRT for the purpose of anti-aging skin treatment. This study aims to examine the intertwined social and cultural contexts influencing menopausal women’s choice of HRT in a dermatological hospital in Ho Chi Minh City, Vietnam. Four dermatologists and 15 menopausal women patients were interviewed regarding their experiences with HRT. Results suggest that skin conditions are closely related with Vietnamese notions of femininity, sexuality, youth, health, and beauty. An ideal skin condition carries cultural auspiciousness, sexual attractiveness, and a positive indication of health. Use of HRT does not merely aim at improving skin condition but also at maintaining beauty and overcoming sexual dysfunction in general—to fix the body from inside. The emphasis on the ideal skin as the key to beauty, sexuality, youth, and social and physical well-being reflects how the female body has been influenced by a social and cultural construction of menopause. While fitting the traditional paradigm of “improving from within,” HRT also repairs women’s sense of luckiness by removing wrinkles, which are perceived as bringing bad luck to family and business. This notion of being lucky enables menopausal women to rebuild their social-sexual agency without being judged against the moral norms for well-behaved older women when they reach menopause.